Who shapes plant biotechnology in Germany? Joint analysis of the evolution of co-authors' and co-inventors' networks - Mariia Shkolnykova (Review of Evolutionary Political Economy, 2020)
The interdependence of science and technology has been of high interest for researchers from different fields for several decades now. As they represent different means of knowledge output protection, patents and research articles generally have different reasons for creation and different audiences. However, some of the inventors may be interested in making an impact on the scientific community and vice versa. This interaction between technology space (patents) and science space (articles) is especially important for high-technology fields, where both research institutions and enterprises play important roles in the innovative environment. This paper investigates the interaction between science and technology in the case of German plant biotechnology. With the help of network analysis tools, the evolution and co-evolution of co-inventors' and co-authors' networks for the period 1995–2015 is explored. Finally, the topics of the patents and papers from the overlap were analyzed with the help of text mining tools in order to identify the differences of topics between science/technology and their overlap. As a result, sizable differences in nature and advancement are observed between the two network types. Although the overlap between these spheres of innovative activities increased over time, the role author-inventors played in the science or technology space varied.
Keywords: O31; O34; D85; 320; Technological space; Science space; Network analysis; Biotechnology; Patents; Bibliometrics